GAMBARAN PENGGUNAAN COMPLEMENTARY ALTERNATIVE MEDICINE (CAM) PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BLAHBATUH II - Ni Nyoman Ayu Devi Suyeni; I Gusti Ayu Agung Septiari; Ni Made Maharianingsih (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Hypertension is an increase in a person's systolic blood pressure ≥ 140 mmHg and diastolic ≥ 90 mmHg. The importance of hypertension sufferers to control blood pressure to prevent cardiovascular risk, one of which is the non-pharmacological alternative of Complementary Alternative Medicine (CAM). This study aims to describe the use of CAM in hypertensive patients in the working area of ​​the Blahbatuh II Health Center. This research method is a non-experimental quantitative descriptive study with a cross-sectional method. The results of this study found that the most use of CAM for the treatment of hypertension in the working area of ​​the Blahbatuh II Health Center were women (59.6%), aged 56-65 years (51.4%), high school education (42.2%), most of them not working/household (33.9%), income ≤ Rp. 2,627,000 (39.4%), suffer from hypertension for 1-5 years (76.1%), have no family history of hypertension (56.9%), hypertension medication, namely amlodipine (52.3%), drinking schedule every day (45.9%). Respondents used CAM since diagnosis (66.1%), CAM was combined with conventional drugs (62.5%) and was recommended by the family (45.8%), the reason that using CAM was very trusting CAM (47.2%), and the reasons for not using CAM were the reasons doctors did not recommend (54.1%), felt a positive effect (94.4%) and were satisfied (94.4%) using CAM. The most common types of CAM were biological therapy in the form of herbs (56.9%), the frequency of using CAM once a day (45.8%), the types of plants used were celery and starfruit (19.5%), plant parts namely leaves (41.5%), the method of processing is boiled first (61%), with a dose of one glass (48.8%) and the use of herbal medicine is taken orally (80.5%). The conclusion of this study was that the sociodemographic characteristics of the use of CAM were mostly aged 56-65 years (51.4%), female sex (59.6%), last education SMK/SMA (42.2%), and the use of CAM was mostly used since suffering from hypertension as many (66.1%) of respondents with the most types of CAM namely biological therapy in the form of herbs (56.9%).